Diagnosis, referral, and primary treatment decisions in newly diagnosed prostate cancer patients in a multidisciplinary diagnostic assessment program - Guy, David; Ghanem, Gabriella; Loblaw, Andrew; Buckley, Roger; Persaud, Beverly; Cheung, Patrick; Chung, Hans; Danjoux, Cyril; Morton, Gerard; Noakes, Jeff; Spevack, Les; Hajek, David; et al. (Canadian Urological Association Journal, 2016)
Introduction: We aimed to report on data from the multidisciplinary diagnostic assessment program (DAP) at the Gale and Graham Wright Prostate Centre (GGWPC) at North York General Hospital (NYGH). We assessed referral, diagnosis, and treatment decisions for newly diagnosed prostate cancer (PCa) patients as seen over time, risk stratification, and clinic type to establish a deeper understanding of current decision-making trends. Methods: From June 2007 to April 2012, 1277 patients who were diagnosed with PCa at the GGWPC were included in this study. Data was collected and reviewed retrospectively using electronic patient records. Results: 1031 of 1260 patients (81.8%) were seen in a multidisciplinary clinic (MDC). Over time, a decrease in low-risk (LR) diagnoses and an increase intermediate-risk (IR) diagnoses was observed (p<0.0001). With respect to overall treatment decisions 474 (37.1%) of patients received primary radiotherapy, 340 (26.6%) received surgical therapy, and 426 (33.4%) had conservative management; 57% of patients who were candidates for active surveillance were managed this way. No significant treatment trends were observed over time (p=0.8440). Significantly, different management decisions were made in those who attended the MDC compared to those who only saw a urologist (p<0.0001). Conclusions: In our DAP, the vast majority of patients presented with screen-detected disease, but there was a gradual shift from low- to intermediate-risk disease over time. Timely multidisciplinary consultation was achievable in over 80% of patients and was associated with different management decisions. We recommend that all patients at risk for prostate cancer be worked up in a multidisciplinary DAP.